An in vivo genetic screen of lung function candidate genes using tissue-specific RNAi in Drosophila melanogaster - Szamek, Emma (2025)
Chronic Obstructive Pulmonary Disease (COPD) is a poorly treatable respiratory condition marked by a progressive and irreversible airflow limitation. The airway epithelium (AE), serving as the first line of defence against inhaled insults, fulfils multiple functions to ensure pulmonary homeostasis. In COPD, the AE is profoundly altered with major changes in epithelial structure and biology that impair barrier function. Given that a significant heritable component underlies disease risk, the identification of genetic factors that alter lung function is crucial to advancing our understanding of COPD pathophysiology and identifying key pathways and targets for therapeutic intervention. The aim of the work described in this thesis is to leverage the relative simplicity, genetic amenability and high-throughput screening potential of transgenic Drosophila melanogaster to elucidate the influence of lung function and COPD-associated genes on epithelial biology. Using an integrative bioinformatics approach, 70 independent lung function GWAS signals were mapped to 187 human candidate causal genes. From these, 60 candidate orthologues of interest were identified in the fly to undergo an in vivo RNAi-mediated knockdown screen in two distinct epithelia: the dorsal thorax and tracheal system. A systematic loss-of-function analysis in the dorsal thorax epithelium revealed a total of 33 genes that disrupt epithelial morphology and behaviour, impacting cell-cell junctions, cell migration and clonal size. Protein-protein interaction analysis of these hits identified regulatory networks prominently associated with ribosome biogenesis and translational control. Notably, ten genes - Rtf1, pAbp, Sec6, Arf102F, RIOK1, Sra-1, INPP5E, CG31759, ssh and RpS26 - emerged as highly penetrant, pivotal regulators of epithelial barrier stability and structural organisation. Further characterisation of cell adhesion found a significant reduction in junctional E-Cadherin levels following Arf102F, Rtf1, RIOK1 and Sra-1 knockdown. A secondary screen of this subset of candidates in the Drosophila tracheal screen identified varied points of developmental arrest. The knockdown of Sec6 and RpS26 specifically resulted in significant airway defects and a reduction in larval body size in the third instar. Expression profiling of human homologues in COPD patient tissues found altered expression in several genes, with pathway analysis linking candidates to previously described regulatory pathways, including MYC and AKT signalling and shared upstream regulators. Finally, preliminary investigations using primary human bronchial epithelial cell culture indicate that EXOC3 (Sec6) and RPS26 (RpS26) knockout may impair epithelial barrier function. Taken together, these findings offer new perspectives on the genetics of COPD and serve as a basis for future translational research using non-mammalian models as a starting point.